On wing sound characteristics and their role in hummingbird communication - Hunter, Todd Alexander (University of Ottawa (Canada), 2004)
The limited ability of humans to decipher the signals produced by other animals has undermined our understanding of the level of communication they possess. Within the avian world, non-vocal sounds have frequently been suggested, as possible forms of communication, but to date have not been tested. Previous studies of hummingbird wing sounds and wing beat frequencies have been limited by technological capabilities and/or sampling effort and have subsequently produced incomplete results. Despite this, several studies have used these questionable results to calculate such things as the relationship between wing length and wing beat frequency. In the absence of a firm understanding of the variability of wing beat frequency within and between individuals of each sex, these studies are subject to an unknown degree of error. Chapter one comprehensively documents the wing sounds of four hummingbird species that breed in Canada. Additionally, I document wing trill characteristics, a new interaction behaviour involving an increase in wing beat frequency and the first account of a wing trill in a female hummingbird. In chapter two, supported by the findings of chapter one, I investigate the role of these non-vocal sounds in intra- and inter-species communication by using wing sounds as playback stimuli. The later chapter's positive communication findings open the door to the field of non-vocal hummingbird communication and beyond into the use of non-vocal communication signals in other avian species.
Keywords: Biology, Zoology.